2020
DOI: 10.1186/s12870-020-02616-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling at osmotic and ionic phases of salt stress response in bread wheat uncovers trait-specific candidate genes

Abstract: Background Bread wheat is one of the most important crops for the human diet, but the increasing soil salinization is causing yield reductions worldwide. Improving salt stress tolerance in wheat requires the elucidation of the mechanistic basis of plant response to this abiotic stress factor. Although several studies have been performed to analyze wheat adaptation to salt stress, there are still some gaps to fully understand the molecular mechanisms from initial signal perception to the onset o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 95 publications
2
37
0
5
Order By: Relevance
“…The osmotic component of the salt stress is believed to dominate at initial stages (several days at least; Munns, 2005), and our findings are in agreement with the fact that the early signaling events in the osmotic phase occur within seconds to hours after salt stress exposure (Duarte-Delgado et al, 2020).Our analysis highlights the co-up-regulation (with a FC of more than 3) of a gene coding for a NAC domain-containing protein (AUR62015630) and three NCED genes (AUR62002735, AUR62037951, AUR62043087) in the shoots of the sensitive Q30. It has been already reported that drought and salt stress caused the induction of NAC domain-containing transcription factors (Iovieno et al, 2016;Shi & Gu, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The osmotic component of the salt stress is believed to dominate at initial stages (several days at least; Munns, 2005), and our findings are in agreement with the fact that the early signaling events in the osmotic phase occur within seconds to hours after salt stress exposure (Duarte-Delgado et al, 2020).Our analysis highlights the co-up-regulation (with a FC of more than 3) of a gene coding for a NAC domain-containing protein (AUR62015630) and three NCED genes (AUR62002735, AUR62037951, AUR62043087) in the shoots of the sensitive Q30. It has been already reported that drought and salt stress caused the induction of NAC domain-containing transcription factors (Iovieno et al, 2016;Shi & Gu, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Here, genes typically involved in the drought response (Balestrini et al, 2019; Iovieno et al, 2016) were found to be regulated. The osmotic component of the salt stress is believed to dominate at initial stages (several days at least; Munns, 2005), and our findings are in agreement with the fact that the early signaling events in the osmotic phase occur within seconds to hours after salt stress exposure (Duarte‐Delgado et al, 2020). Our analysis highlights the co‐up‐regulation (with a FC of more than 3) of a gene coding for a NAC domain‐containing protein (AUR62015630) and three NCED genes (AUR62002735, AUR62037951, AUR62043087) in the shoots of the sensitive Q30.…”
Section: Discussionsupporting
confidence: 90%
“…The STEM clustering method was applied to analyze the expression patterns of DEGs in the bovine mammary gland during the period of lactation decline [ 14 , 32 ]. Each gene was assigned to the closest profile using a Pearson correlation-based distance metric.…”
Section: Methodsmentioning
confidence: 99%
“…We, therefore, conclude that these resistance loci can be a potential starting point to impart environment friendly and climate smart WBM resistance in wheat. In addition, arrival of many new technologies such as MACE (Massive Analysis of cDNA 3′ ends) and RNA -sequencing (Duarte-Delgado et al, 2020) may help to understand the mechanisms behind the resistance loci being reported.…”
Section: Genetic Analysesmentioning
confidence: 99%